Perceived usefulness of open educational resources: Impact of switching to online learning for face-to-face and distance learners - Cheung, Simon K. S.; Wong, Billy T. M.; Li, Kam Cheong (Frontiers in Psychology, 2023)
This paper reports a study on the perceived usefulness of university students on open educational resources (OER) in relation to the switch of learning mode to online learning during the COVID-19 pandemic. The participants involved two groups of students, one studying in a face-to-face mode and the other in a distance learning mode. They took part in a survey which was conducted in 2019 before the pandemic (with a total of 912 responses) and 2021 during the pandemic (with a total of 1,018 responses). The results show that both groups of students generally perceived OER to be more useful during the pandemic. The specific types of OER which were perceived as relatively more useful include open online courses and open access textbooks. Face-to-face students showed a higher level of perceived usefulness of OER for preparing tests and examinations, while distance learning students perceived OER as more useful for supplementing course materials. They both concerned about the limitations of OER, especially on accuracy and comprehensiveness. The findings suggest the importance of recognizing the diverse needs of the two groups of students and offering appropriate OER support for them.